Genome-wide methylation analysis of retrocopy-associated CpG islands and their genomic environment. Issue 3 (3rd March 2016) - Grothaus, Katrin; Kanber, Deniz; Gellhaus, Alexandra; Mikat, Barbara; Kolarova, Julia; Siebert, Reiner; Wieczorek, Dagmar; Horsthemke, Bernhard
ABSTRACT: Gene duplication by retrotransposition, i.e., the reverse transcription of an mRNA and integration of the cDNA into the genome, is an important mechanism in evolution. Based on whole-genome bisulfite sequencing of monocyte DNA, we have investigated the methylation state of all CpG islands (CGIs) associated with a retrocopy (n = 1, 319), their genomic environment, as well as the CGIs associated with the ancestral genes. Approximately 10% of retrocopies are associated with a CGI. Whereas almost all CGIs of the human genome are unmethylated, 68% of the CGIs associated with a retrocopy are methylated. In retrocopies resulting from multiple retrotranspositions of the same ancestral gene, the methylation state of the CGI often differs. There is a strong positive correlation between the methylation state of the CGI/retrocopy and their genomic environment, suggesting that the methylation state of the integration site determined the methylation state of the CGI/retrocopy, or that methylation of the retrocopy by a host defense mechanism has spread into the adjacent regions. Only a minor fraction of CGI/retrocopies (n = 195) has intermediate methylation levels. Among these, the previously reported CGI/retrocopy in intron 2 of the RB1 gene ( PPP1R26P1 ) as well as the CGI associated with the retrocopy RPS2P32 identified in this study carry a maternal methylation imprint. In conclusion, these findings shed light on the evolutionary dynamics and constraints of DNA methylation.